Aproximações entre a educação e o movimento ciência, tecnologia e sociedade : um olhar sobre dissertações e teses no ensino de química - Carmo, Tânia do (2014)
The approach between Environmental Education and the Science, Technology and Society Movement and its contributions on the teaching of Chemistry is discussed. It is a strategy in the formation of critical individuals who will also face current environmental challenges. Current study aims at the extant approaches between the two teaching perspectives for the enhancement of teaching for the critical and reflexive formation of environmental issues which require new strategies to be solved. Current qualitative and bibliographic research was foregrounded on one doctoral thesis and nineteen master´s dissertations on Environmental Education and the Science, Technology and Society Movement from the perspective of Contents Analysis. Four a priori categories were employed for the organization and discussion of results, which deal with chemical knowledge and contexualization for the understanding and transformation of social reality. The analysis showed a considerable occurrence in research on the two perspectives on social and environmental issues such as wastes, water, pollution, forest fires and toxic fertilizers, coupled to the inter-relationships between these themes and human activity impacting the environment. Results demonstrate that the development of formation based on the approach of these two movements is a significant strategy to analyze the life of teachers and students within a critical perspective for the transformation of physical and society reality. However, there are still significant barriers that contribute towards the impairment of such pedagogical activity on the teacher-student integration and on social and environmental aspects.